Multifunctional Nanoassemblies for Cytotoxic Drug and Therapeutic Enzymes Delivery in Neuroblastoma Therapy. Issue 1 (9th September 2022) - Parra‐Nieto, Jorge; García del Cid, María Amor; Galeano, Carolina; de Carcer, Iñigo Aguirre; García‐García, Lorena; Gonzalez‐Murillo, África; Megias, Diego; Ramirez, Manuel; Baeza, Alejandro
Abstract: Neuroblastoma cells can acquire resistance mechanisms that make them invulnerable to chemotherapeutic agents. The use of nanoparticles as drug carriers provides the possibility to deliver several drugs simultaneously to specific tumoral cell populations, improving their therapeutic outcome. Herein, the development of a multifunctional nanoplatform based on the assembly of protocells (PC) and polymeric nanocapsules (PNC) is reported. PC provides the ability to transport and release cytotoxic drugs while PNC offers the capacity to transport enzymes to the tumoral tissues preserving their catalytic activity. Doxorubicin (Dox) and Glucose Oxidase (Gox) are housed within PC and PNC, respectively. The external surface of these nanoassemblies is decorated with synthetic targeting moieties, providing selectivity to neuroblastoma cells. Thus, the nanoplatform is endowed with the ability to generate multiple insults within neuroblastoma cells as cytotoxic drug release, glucose starvation, and oxidative damage. This nanoplatform exhibits significantly higher cytotoxic activity in comparison with only drug‐loaded protocells or empty protocells decorated with glucose oxidase nanocapsules, which points out the existence of a potent synergic effect between the action of both therapeutic agents: Dox and Gox. This strategy can be adapted to the production of multifunctional nanoassemblies, improving the arsenal against different types of tumors. Abstract : A multifunctional nanoplatform based on the assembly of doxorubicin‐loaded protocells (PC) and polymeric nanocapsules (PNC) which contain glucose oxidase is developed. Synthetic targeting moieties located on the external surface provide the selectivity toward neuroblastoma cells. The synergic effect caused by doxorubicin release, glucose starvation, and oxidative damage induces a potent cytotoxic effect which provokes the destruction of the tumoral cells.